The efficacy of furmonertinib in untreated advanced NSCLC patients with sensitive EGFR mutations in a real-world setting: a single institutional experience - Yan, Ningning; Guo, Sanxing; Huang, Siyuan; Zhang, Huixian; Li, Xingya (Frontiers in Oncology, 2024)
Background: Furmonertinib is the standard treatment option in the first-line setting for advanced non-small cell lung cancer (NSCLC) with sensitive epidermal growth factor receptor (EGFR) mutations in China. However, there is limited real-world data available. Methods: We conducted a retrospective study at a single center, analyzing a cohort of 73 NSCLC patients who tested positive for EGFR mutations and were treated with Furmonertinib as their initial therapy between August 2022 and December 2023. The primary endpoint was progression-free survival (PFS), with secondary endpoints including objective response rates (ORR), overall survival (OS), and safety profile. Results: The median observation period was 9 months (95% confidence interval [CI] 8.0-20.0). The median PFS was 19.5 months (95%CI, 14.6 – 24.4). OS data was not yet mature. Univariate analysis showed no significant correlation between PFS and factors such as ECOG PS score, presence of brain or liver metastases, sex, age, EGFR mutation status, or number of metastatic sites. However, multivariate analysis indicated a potential trend towards extended PFS in patients younger than 65 years (p=0.053, 95%CI, 0.10-1.02), although the p-value was only marginally significant. The most common adverse events were diarrhea (24%), anemia (36%), and liver injury (32%); however, only four cases experienced severe adverse events. Conclusion: In a real-world setting, Furmonertinib appears to be a favorable treatment option for EGFR-mutated patients. The manageable nature of adverse events further supports its use in clinical practice.